Delineating an Unmarked Graveyard by High-Resolution GPR and pXRF Prospection: The Medieval Church Site of Furulund in Norway - Rebecca J.S. Cannell; Lars Gustavsen; Monica Kristiansen; Erich Nau (Journal of Computer Applications in Archaeology, 2018)
The lack of accurate locational information on abandoned medieval and later graveyards constitutes a considerable challenge to national and local bodies tasked with their protection and management. These sites are increasingly in danger of destruction due to climatic changes, intensified farming schemes or developmental encroachment, and there is an ever-growing need to develop nonintrusive methods to ensure their detection and delineation so that they can be protected. In 2014, the Norwegian Directorate for Cultural Heritage received alarming information on the worsening state of the medieval church site at Furulund, in the southeast of the country. A successful, cost-effective campaign using high-resolution, large-scale georadar surveys in conjunction with geochemical mapping using portable XRF was undertaken in order to delineate and characterise the graveyard so that remedial actions could be initiated and the graveyard protected. Whilst the interpretations are unique to the site, the method combination has the potential to effectively resolve detection and protection of other, similar sites in Norway and beyond.